PENGARUH CORPORATE GOVERNANCE DAN RASIO AKUNTANSI TERHADAP PERINGKAT OBLIGASI - Damayanti, Eka Wahyu; Fitriyah, Fitriyah (Fakultas Ekonomi, UIN Maliki Malang, 2013)
This research was aimed to examine the effect of good corporate governance and the accounting ratios that partially or simultaneously are concerned with bond credit ratings. The population in this research are are all the companies rated by PT.PEFINDO over the period 2010 to 2011. Sampling using a purposive sampling technique and number of sample are 42 companies. The analysis method of logistic regression is used for measuring the effect of good corporate governance, the financial ratios and bond credit ratings. The result shows, the value of the Adjusted R Square of 0,45 or 45% indicates that the independent variable, namely corporate governance and accounting ratios, can explain the dependent variable bond ratings by 45% while the remaining 55% is explained by other factors outside the model studied. Significant variable are the board, audit committe, the company’s growth in the proxy by ROA, Leverage ratio in proxy by DER, Slovency ratio and Liquidity ratio. This situation is based upon the significant number of 0,05, while the variables that are not significant are the NPM variables, Sales to Asset, Institutional ownership, managerial ownership and the size of the board of commissioners.